Pulmonary clinical case - Amaro,Catarina de Abreu (2022)
Abstract Post-extubation acute pulmonary edema (PEAPE) is an uncommon complication of tracheal extubation, occurring in 0.1% of patients undergoing general anesthesia. It has rarely been described in pediatric age, but its incidence is thought to be underestimated, as many cases of post-operative respiratory distress may be misdiagnosed or unrecognized. A formerly healthy 15-year-old male diagnosed with acute appendicitis was submitted to a laparoscopic appendectomy under general anesthesia. Immediately after extubation, he developed signs and symptoms of respiratory distress, and chest radiograph was compatible with acute pulmonary edema. Due to suspicion of PEAPE, supplementary oxygen and intravenous furosemide were administered, with favorable outcome. PEAPE is a major anesthesia-related emergency, which may worsen the prognosis of low-risk surgical procedures. A high degree of suspicion should be maintained in children and adolescents presenting with signs of respiratory distress and hypoxia after general anesthesia, as prompt diagnosis and treatment are crucial for a favorable outcome.